A case report on alcohol and crime in the Transkei region of South Africa - BL Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Alcohol and crime are two-in-one, inseparable from each other as most of the crime in South Africa is carried out under the influence of alcohol. Many deaths as well in South Africa are attributed to alcohol consumption but, despite that, alcohol is available everywhere in country. Objective: To highlight the problem of alcohol and crime in the Transkei region of South Africa. Method: This case study is based on the case report histories which were obtained from the Mthatha Forensic Pathology Laboratory. Results: These are ten cases that provide examples of alcohol related deaths. All these deaths were caused by stabbing (except one) where the perpetrator or victim or both were intoxicated. The primary underlying cause of these fight was either money or girlfriends. The history, culture and circumstances of these deaths are discussed in this manuscript. Conclusion: Alcohol is a major cause of crime in the Transkei region of South Africa.